Correlation Between Milk and Blood Urea Nitrogen in High and Low Yielding Dairy Cows - Sosa Puente, Irene Beatriz (2010)
A study was carried out in two dairy farms (Olocuilta and Los Conacastes) in the central region of El Salvador. Sixty Holstein cows were grouped according to milk yield and days in milk: high yielding (HY, 30–90 d in milk) and low yielding cows (LY, >180 d in milk). The objective of the study was to evaluate the effect of milk yield and time after feeding on milk and blood urea-nitrogen (BUN) concentration, and to establish a correlation between these two parameters. On Olocuilta, HY cows had the highest BUN and milk urea nitrogen (MUN) concentrations. Blood urea nitrogen least squares concentration was 12.77 mg/dL and 13.98 mg/dL for the LY and HY cows, respectively; while the MUN average concentration was 12.30 mg/dL and 14.82 mg/dL for the LY and HY cows, respectively. BUN and MUN concentrations were similar at 30 min, one and two h post-feeding but by four h post-feeding BUN concentrations had decreased and were significantly lower than those of MUN (P < 0.05). On the other hand, in Conacastes the highest values were found for the LY group. BUN least square concentration was 11.22 mg/dL and 9.12 mg/dL for the LY and HY cows, respectively; while the MUN average concentration was 10.18 mg/dL and 8.83 mg/dL for the LY and HY cows, respectively. The reason for these differences seems to be related to protein balance. For instance on the Los Conacastes farm, protein balance was negative in the HY group (-88 g/d) while on Oloculita farm the balance was positive. The correlation between BUN and MUN for the Olocuilta farm had a regression coefficient of 0.84, and a correlation (r2) of 0.7543. For Los Conacastes these values were 1.04 and 0.9017, respectively. It should be noted that BUN and MUN concentrations were better correlated at 30 min, one h and two h after feeding and that the correlation decreased at four h post-feeding due to a drop in BUN concentration. It is concluded that BUN and MUN concentrations are not related directly to milk yield but with the protein balance. There was a high correlation between BUN and MUN concentrations; hence, either of these parameters can be used to monitor protein nutrition in dairy farms.